Can an economic activities inventory fill the knowledge gap about the economic sector in a policy making process? - Giaretta, Federico; Zaman, Jan (My University, 2017)
Wirtschaftliche Aktivitäten spielen in Städten und ihren Vororten eine wichtige Rolle, die nach Ansicht der Autoren im Gegensatz zu den Wohnfunktionen der Stadt nicht angemessen gewürdigt werden. Am Beispiel Brüssels schlagen sie vor, Wirtschaftsaktivitäten im Stadtraum mittels GIS-Techniken zu erfassen und zu visualisieren. Vorgestellt wird ein Pilotprojekt eines für die Stadtentwicklung und Stadt- und Regionalplanung nutzbaren Inventars der Wirtschaftsaktivitäten in Brüssel und der Region Flandern.

Nowadays, Brussels' population is growing and requires more and more space for housing. This constantly growing process tend to push the industrial and medium / large economic activities out of the city. These activities are wrongly perceived to be unsightly for an urban environment. Economic activities, often mixed with other functions play an important role within cities and their suburbs areas. However this role is not well understood. For that reason an analysis that identifies the different types of activities and their location can be fundamental in the early phase of a urban development project, to give at all the stakeholders a better and more complete view. This work is based on the will to get a better and new kind of knowledge about the location and differentiation of economic activities in Brussels metropolitan northern area. The visualization of the diversity of types and scales of economic activities, and understanding trends and dynamics, can be considered as a useful set of information to be used in a urban development and economic policy making process. The work, conceived as a pilot project, which could be extended and repeated in other areas, is based on an empirical research, done by a visual check of what is identifiable as economic or designed for an economic use directly on the site, aimed to identify, locate and classify all the different types of existing economic activities in the selected areas. This economic activities inventory is the only one existing for Brussels capital and Flanders regions based on field work. The paper explains the method used for the field work and inventarisation, the possible link with existing economic databases and the difficulties encountered during the work. It also shows how this new data is used in ongoing spatial planning processes and to what extend these new insights promote different spatial planning proposals and realisations.
Keywords: Stadtökonomie; Regionalwirtschaft; Wirtschaftsgeografie; Gewerbeansiedlung; Standort; Regionale Daten; Datendokumentation; Datenbank; Geoinformationssystem; GIS; Wirtschaftsstandort; Visualisierung; Inventar